(untitled) (Research, Society and Development, 2023)
In line with the concept of interdisciplinarity, the present work proposes a simple experiment to teach solid decomposition reactions, through the geometric evolution of naphthalene parallelepipeds submitted to sublimation. Geometric modeling of the specimen’s face projections by the Lamé curves (also called superelipses) allows the calculation of the volume of the corresponding superelipsoid, resulting in adequate quantification of the evolution of the naphthalene sample mass. The proposed experimental procedure has proved to be a simple and elucidative tool for carrying out practical classes in the laboratory, minimally equipped, aiming at learning both solid decomposition reactions and mathematical modeling techniques for heterogeneous reaction interfaces, using Lamé curves.